Matrix-targeting immunotherapy controls tumor growth and spread by switching macrophage phenotype - Deligne, Claire (Cancer Immunol Res, 2020)
The interplay between cancer cells and immune cells is a key determinant of tumor survival. Here, we uncovered how tumors exploit the immuno-modulatory properties of the extracellular matrix to create a microenvironment that enables their escape from immune surveillance. Using orthotopic grafting of mammary tumor cells in immunocompetent mice and autochthonous models of breast cancer, we discovered how tenascin-C, a matrix molecule absent from most healthy adult tissues but expressed at high levels and associated with poor patient prognosis in many solid cancers, controls the immune status of the tumor microenvironment. We found that, although host-derived tenascin-C promoted immunity via recruitment of pro-inflammatory, antitumoral macrophages, tumor-derived tenascin-C subverted host defense by polarizing tumor-associated macrophages towards a pathogenic, immune-suppressive phenotype. Therapeutic monoclonal antibodies that blocked tenascin-C activation of toll-like receptor 4 reversed this phenotypic switch in vitro and reduced tumor growth and lung metastasis in vivo, providing enhanced benefit in combination with anti–PD-L1 over either treatment alone. Combined tenascin-C:macrophage gene expression signatures delineated a significant survival benefit in people with breast cancer. These data revealed a new approach to targeting tumor-specific macrophage polarization that may be effective in controlling the growth and spread of breast tumors.